2020
DOI: 10.1093/ajhp/zxaa287
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis and use of argatroban for the treatment of massive pulmonary embolism following anticoagulation failure in a patient with COVID-19

Abstract: Disclaimer In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The infected immune cells respond with cytokine production, and autophagy 33 . Interestingly, a higher rate of reported pulmonary embolism and thrombosis in patients with severe COVID19 [34][35][36] may be attributed to platelet activation after direct infection with the virus and secondary autophagy 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The infected immune cells respond with cytokine production, and autophagy 33 . Interestingly, a higher rate of reported pulmonary embolism and thrombosis in patients with severe COVID19 [34][35][36] may be attributed to platelet activation after direct infection with the virus and secondary autophagy 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…While every effort is being made by the medical experts to treat patients by taking suitable preventive measures employing anticoagulation therapeutics to deal with the coagulation issues. Despite superb benefits with the use of systemic anticoagulation therapies, the data seem to be retrospective in nature thus raising some questions on the possible interplay of other confounders, as well as, long-term benefits and safety of the systemic anticoagulation approach [26][27][28][29][30][31][32][33][34].…”
Section: Proteinase and Covid-19mentioning
confidence: 99%
“…Moreover, reduced levels of antithrombin, a protein involved in the regulation of the coagulation cascade, have been reported in COVID-19 patients ( Arachchillage et al, 2020 ). Interestingly, according to recent findings, treatment with Argatroban, a direct thrombin inhibitor with anticoagulant effects independent from antithrombin, seems to provide significant therapeutic effects in patients ( Arachchillage et al, 2020 ; Sagardia and Daniels, 2020 ), albeit this drug was shown to be unable to inhibit SARS-CoV-2 replication (NIH 8 ). As the pandemic is spreading, the reported coagulation disorders in COVID-19 patients as in previous SARS and MERS patients should be carefully addressed.…”
Section: Resultsmentioning
confidence: 99%